PRELIMINARY STUDY THE EFFECT OF MULTILEAF COLLIMATOR (MLC) TRANSMISSION ON DOSE CALCULATION BASICLY - NISA (NIM : 20212003); Pembimbing : Dr. rer.nat Freddy Haryanto, CHAIRUN
The main goal of radiotherapy treatment is the irradiation of a target volume while minimizing the amount of radiation absorbed in healthy tissue. Multileaf Collimator (MLC) is one of method to achieve this goal. This study aims to investigate the effect of MLC transmission on dose calculation in Prism TPS MLC transmission can be investigated by measuring the dose at depth of dmax while MLC leaves open with field size of 10 x 10 cm2 and closed with field size 0.6 x 40 cm2 at SSD 100 cm , then compare between them and see how the dose distribution in the profile graph. In this study do several variations they are energy, field size, profile depth and monitors unit. Based on dose calculation have done by Prism, MLC transmission effected by energy, field size, profile depth and monitors unit